2021
DOI: 10.3389/fmicb.2021.717809
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Occurrence and Spread of Antibiotic Resistance in Wastewaters and in Wastewater Treatment Plants: Mechanisms and Perspectives

Abstract: This paper reviews current knowledge on sources, spread and removal mechanisms of antibiotic resistance genes (ARGs) in microbial communities of wastewaters, treatment plants and downstream recipients. Antibiotic is the most important tool to cure bacterial infections in humans and animals. The over- and misuse of antibiotics have played a major role in the development, spread, and prevalence of antibiotic resistance (AR) in the microbiomes of humans and animals, and microbial ecosystems worldwide. AR can be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 203 publications
0
69
0
1
Order By: Relevance
“…When ARGs are transmitted into human-associated pathogens, they may pose a great environmental risk [ 22 ]. Many ARGs and other potentially harmful functional genes are spread through the environment by horizontal gene transfer (HGT) [ 23 25 ]. However, the current knowledge on HGT events in aquaculture models, especially those involving multi-kingdom microbes and ARGs, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…When ARGs are transmitted into human-associated pathogens, they may pose a great environmental risk [ 22 ]. Many ARGs and other potentially harmful functional genes are spread through the environment by horizontal gene transfer (HGT) [ 23 25 ]. However, the current knowledge on HGT events in aquaculture models, especially those involving multi-kingdom microbes and ARGs, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Finding replication and mobility proteins was expected as they form the backbone of plasmids, however finding several TA systems was not expected. TA systems can be thought of as selfish genetic elements, securing the stability of the plasmid carrying it through post-segregation killing 78 . It could be speculated that the relative abundance of TA systems correlates to the small size distribution of our plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently indicated that methicillin resistance emerged in Staphylococcus aureus in hedgehogs as an adaptation to beta-lactam-producing dermatophyte 79 highlights the coevolution among microbes in natural habitats as important sources of AMR emergence. A high percentage of antibiotics are not fully metabolized in humans, and macrolides have been detected in wastewater 80,81 , though wastewater treatment plants lower their abundance 81,82 .…”
Section: Global Arg Occurrencementioning
confidence: 99%
“…Whichever treatment is used, the process is not targeted at emerging compounds (pharmaceuticals, personal care products), bacteria or their genes but aims to remove organic components, nutrients (P, N) and suspended solids. Differences in treatment plant design and operation influence the fate of ARB and ARGs in wastewater; conventional activated sludge treatment combined with advanced treatment methods—such as UV or ozonation—show improved removal of ARB and ARGs compared to activated sludge alone [ 137 , 140 , 148 ]. A recent review by Pai et al [ 149 ] estimates the removal of ARGs to be 0.1–0.6 log units with primary treatment, 1–2 log units with secondary treatment and 0–6 log units with advanced treatment methods.…”
Section: Antimicrobial Resistance In the Environmentmentioning
confidence: 99%
“…Some antimicrobials, such as sulphonamides, fluoroquinolones, erythromycin and tetracycline are preferentially removed into the sludge, either by physical adsorption or enhanced adsorption through addition of flocculants [ 167 , 168 , 169 , 170 ]. The fate of ARB and ARGs through wastewater systems, including sludge, has been extensively studied, with the focus often on a small number of resistance genes or specific bacterial species [ 137 , 148 ]. Results are usually very dependent on the system studied and cannot easily be extrapolated to other WWTP and AMR determinants.…”
Section: Antimicrobial Resistance In the Environmentmentioning
confidence: 99%